Penerapan asas kesukarelaan dalam konseling kasus pacaran beresiko pada remaja - I Gst. Agung Diah Rusdayanti; Kadek Suranata; I Ketut Dharsana (Indonesian Institute for Counseling, Education and Therapy (IICET), 2023)
Problems experienced by adolescents in courtship relationships are risks that tend to lead to negative impacts. Adolescent volunteerism must seek help to solve problems in courtship. The counseling process in adolescent education can accompany and direct adolescents toward problem-solving. The purpose of this literature review research is to know the implementation of the principle of volunteerism in counseling, the impact of risky courtship on adolescents, and the application of the principle of volunteerism in counseling cases of risky courtship in adolescents. The method used in this article is a literature review. The research data is sourced from data mining techniques with a literature review. The result of this literature review is that the implementation of the principle of volunteerism in counseling takes place based on volunteerism and without being forced both by the counselor and the counselee. The impact of at-risk courtship on adolescents consists of physical, psychological, and social impacts. Applying the principle of volunteerism in counseling cases of risky courtship in adolescents is carried out by the counseling process. The counseling process is divided into three stages, namely, the initial stage of counseling, the middle stage, and the final stage of counseling. In the early stages of counseling, the counselor builds a good relationship and communication with the counselee, accompanied by an assessment and delivery of the principle of volunteerism for data mining related to counseling problems. The middle stage of counseling is the core stage of counseling activities which is accompanied by the intervention of behavioral approach counseling with one of the behavioral approach techniques, namely assertive training techniques for handling cases of risky courtship. In the final stage of counseling, the counselee makes decisions for themselves based on consideration of alternative solution options provided by the counselor.